2016
DOI: 10.1080/17518253.2016.1180432
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide blackcurrant seed extract as an anti-irritant additive for hand dishwashing liquids

Abstract: The study investigated the effect of hydrophobic, blackcurrant seed extract (Ribes nigrum L.) obtained under supercritical CO 2 conditions on the anti-irritant properties of hand dishwashing liquids. A range of liquids differing in extract concentration (0-0.5 wt%) were prepared. The product prototypes were subjected to tests focusing on their anti-irritating property and functionality. Based on the zein values and measurements of changes in the pH level of the bovine albumin solution, the liquids were shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…The ability to emulsify fatty soils was tested according to the Polish standard PN‐C‐77003: 1997. The research methodology was described by Wasilewski and co‐authors (Wasilewski et al, , b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to emulsify fatty soils was tested according to the Polish standard PN‐C‐77003: 1997. The research methodology was described by Wasilewski and co‐authors (Wasilewski et al, , b).…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the irritation potential of cosmetics containing anionic surfactants in these types of products, mixtures of different surfactants, polymers, emollients, and hydrophobic substances are used (Bujak et al, , ; Draelos et al, ; Fevola et al, ; Klimaszewska et al, , , b; Seweryn, ; Seweryn and Bujak, ; Walters et al, ; Wasilewski et al, , b). Among natural polymers one can distinguish the proposed in the article Klimaszewska et al (Klimaszewska et al, ) marine collagen with various molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…The final result (mean value of three independent measurements) obtained in the test determining the ability of the evaluated formulation to emulsify fatty soils was expressed in grams of oil per liter of the evaluated formulation at a concentration of 1 wt.%. The test methodology was described by Seweryn et al (Seweryn and Bujak, 2018;Seweryn et al, 2016) and Wasilewski et al (Wasilewski et al, 2016c, 2018a.…”
Section: Evaluation Of Ability To Emulsify Fatty Soilsmentioning
confidence: 99%
“…Based on the Author's own experience in the production technology of hand dishwashing liquids (Seweryn et al, 2016;Wasilewski et al, 2016cWasilewski et al, , 2016d and the available literature (Blagojevi c et al, 2016;Gambogi et al, 2006;Shi et al, 2006), prototypical product formulations were developed. The compositions of the formulations are shown in Table 1.…”
Section: Formulations and Technology For Producing Hand Dishwashing Lmentioning
confidence: 99%
“…There are literature reports evaluating the effect of plant extracts produced under supercritical CO 2 conditions on the properties of various household chemical products (Jang and Lee, ; Pajnik et al, ; Seweryn et al, ; Wasilewski et al, , b, c, d). In their studies, Wasilewski et al (Seweryn et al, , Wasilewski et al, , b, c, d) used hydrophobic supercritical CO 2 plant extracts in hand dishwashing liquids. The authors observed that the incorporation of hydrophobic plant extracts (Fragaria ananassa CO 2 extract, Ribes nigrum CO 2 extract, Aronia melanocarpa CO 2 extract) into hand dishwashing liquid formulations significantly modified their rheological properties.…”
Section: Introductionmentioning
confidence: 99%